Concept of Environmental Communications in the Environmental Rewards Mechanism to Build Harmonic Relations Between the Hulu – Hilir Communities in the Cidanau Watershed - Rahmi Winangsih; Rahmi Mulyasih; Rethorika Berthanila; F Fuqoha; M Marthalena; Indrianti Azhar Firdausi (Future Science, 2022)
Environmental communication is indispensable for human development at this time, this cannot be separated from the declining quality and quantity of natural resources in the community. Therefore, the mechanism for rewarding environmental services is a new system that can support the preservation of the environment because the reward for environmental services will form cooperation between the upstream community as a group that maintains and preserves the environment so that the environmental ecosystem is maintained with downstream communities who enjoy natural resources that are protected by the community. upstream. The purpose of this research is to focus more on how FKDC can implement environmental communication so that communication between upstream and downstream communities can be harmoniously established. The results of the research show that the environmental communication implemented by FKDC is running optimally, this can be seen from the environmental service mechanism process that has been running for ten years